ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN KARIR KARYAWAN: (Studi Pada PT. Bank Rakyat Indonesia (BRI) Cabang Sampang) - Rizqul Karimah; Sayekti Suindyah; Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 46 employees. The objectives of this study are 1). To find a description of the object / research subject 2). To test and analyze the simultaneous influence of work performance, work ability and education with employee career development at PT. Bank Rakyat Indonesia (BRI) Sampang Branch. 3). To test and analyze the relationship between the influence of job performance and career development of employees at PT. Bank Rakyat Indonesia (BRI) Sampang Branch. 4). To test and analyze the relationship between the influence of work ability and career development of employees at PT. Bank Rakyat Indonesia (BRI) Sampang Branch. 5). To test and analyze the relationship between the influence of education and career development of employees at PT. Bank Rakyat Indonesia (BRI) Sampang Branch. 6). To test and analyze which variables between job performance, work ability and education have a dominant influence on employee career development at PT. Bank Rakyat Indonesia (BRI) Sampang Branch. The results showed that